Pengembangan Aplikasi Cerita Rakyat Daerah Berbasis Mobile TriPanca - Ahmad Mustofa Hadi Romadhoni; I Gede Ardhy Niratha; Muhammad Abdurrafi; Taufiqur Ramadhan; Danish Adli El Said; Florentina Yuni Arini (LPPM Universitas Bina Sarana Informatika, 2025)
Preserving local culture faces challenges in the era of globalization and digitalization, especially for the younger generation who are more familiar with foreign popular culture. Folklore, as an intangible cultural heritage rich in moral values ​​and cultural identity, is increasingly marginalized due to the lack of attractive media. This study develops TriPanca an interactive mobile application based on folklore with a User-Centered Design (UCD) approach to meet the needs of the younger generation. The development process includes user needs analysis, prototype design, and iterative evaluation. This application is equipped with story list, search, favorites, and user profile features. Testing shows that UCD is effective in increasing user interest, making this application an interactive educational tool as well as a medium for preserving local culture in the digital era.